DESIGN AND ANALYSIS MODEL APPLICATION SYSTEM TEACHING MEDIA ONLINE - Fitria Fitria; Sri Lestari; Hendra Kurniawan; M Ariza Eka Y (Prosiding International conference on Information Technology and Business (ICITB), 2016)
Education is very important for the formation of a developed country with HR (Human Resources) were superior. Education is also a provision to compete in the world of work, especially in higher education. But education at the college level, both public and private sector can not be felt by all citizens of Indonesia who have graduated from educational level of SMA / SMK / MA this Sederajat.Saat IBI Darmajaya not yet have a facility that serves the community outside the campus IBI Darmajaya, especially graduates SMA / SMK / MA who want to learn more about the lecture material corresponding departments in IBI Darmajaya, but they do not have the opportunity to come and study at the campus IBI Darmajaya. Therefore, the need for an online instructional media (E-learning) that can facilitate them to learn and gain knowledge as male and female students who enrolled diperguruan particularly high in IBI Darmajaya. Media teaching online (e-learning) is built using PHP, MySQL, and while the bootstrap method is the prototype development. Media's online resource will provide convenience for those who want to learn and acquire materials and communicate with faculty who are competent in their field.KEY WORDS: Instructional Media Online (E-learning), Education, Prototype.